From histories of museums to museum history: approaches to historicising colonial museums in Aotearoa New Zealand. Issue 1 (2nd January 2020) - McCarthy, Conal
ABSTRACT: Despite their reputation for stasis and fixity, museums are about change and transformation. What can we learn from the history of New Zealand museums about the study of museum history? This article considers the lessons we can glean from New Zealand museums in the colonial period. It surveys recent theories about history, social change and museums, including historical sociology, which throw much light on this topic and open up new future paths to explore. The aim is not the compiling of an institutional history but to propose a refined analytical framework for museum history which can deal with the constant change which characterises the history of museums. It argues that we need to move beyond both the conventional idea of a linear history, and also the reliance on commemoration, in order to do 'museum history', rather than just 'histories of museums'. This approach is explicitly interdisciplinary, explores historical and theoretical perspectives on museums, and considers their implications for current museum practice. By historicising museums, both their internal practices and their external social relations, we may move beyond the commemorative histories of museums to develop a critical museum history. This new museum history needs to interrogate the past, not describe, commemorate and celebrate it.